Real estate market - Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2023)
This short article provides a quick summary of the studies of real estate markets. Some new developments are also discussed.
Keywords: D80; R20; R30; 330; centralized versus decentralized markets; search-theoretic models; match; policy